Módulo de Administración y Adquisiciones para el Sistema Unificado de Administración y Gestión de las Bibliotecas de la Universidad Nacional de Loja. - Ortega SAntín, Yadira Nathalie (2011)
The present work is a project of development of software for the administration and management librarian, with the purpose of standardizing the above mentioned processes inside Loja's National University, in gun-sights of satisfying one of his more commanding needs; the same one who understands in his general content; the object of investigation, methodology, theoretical foundation, and other technical documentation developed for the obtaining of the final product. The project there has been developed on the base of the latent reality of the libraries of Alma Mater, with innovative technology, capable of offering to the university community a qualit product, which allows the improvement of the processes librarians understood to general level in two categories: procedures of internal type (technical services, as acquisition, organization and physical treatment of the material librarian) and the modals to users' administration; with which we want to help to give major embossment to so prestigious center of to know.